1983
DOI: 10.1111/j.1365-2125.1983.tb02151.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of valproic acid in young and elderly subjects.

Abstract: The disposition of valproic acid was studied following single dose intravenous administration in seven young male volunteers aged 20‐35 years and six elderly male in‐patients aged 75‐87 years. Following administration of 400 mg sodium valproate, blood samples were collected for 48 h and valproic acid concentrations analysed by enzymatic immunoassay. The median elimination half‐life was 7.2 h in the young subjects but 14.9 h in the elderly patients (P less than 0.01). However, clearance did not differ significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 4 publications
1
36
0
2
Order By: Relevance
“…The discrepancies between our findings and those reported in the previous study cannot be explained by differences in route of administration: in fact, VPA is known to be completely absorbed from the gastro-intestinal tract in young subjects (Perucca et al, 1978a, b) and a possible reduction of bioavailability in the elderly would have resulted in overestimation rather than underestimation of its volume of distribution. On inspection of the data presented by Bryson et al (1983) it is also unlikely that differences in type of kinetic analysis (calculation of Vd s, or volume of distribution at steady-state, rather than Vd) could account for the observed discrepancies. It can be concluded that the latter were probably related to the characteristics of the populations investigated: it is unclear, for example, whether the elderly patients included in the earlier study were ambulant or bedridden and whether they were receiving associated drug therapy (although it was stated that none was taking drugs 'likely to interact' with VPA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancies between our findings and those reported in the previous study cannot be explained by differences in route of administration: in fact, VPA is known to be completely absorbed from the gastro-intestinal tract in young subjects (Perucca et al, 1978a, b) and a possible reduction of bioavailability in the elderly would have resulted in overestimation rather than underestimation of its volume of distribution. On inspection of the data presented by Bryson et al (1983) it is also unlikely that differences in type of kinetic analysis (calculation of Vd s, or volume of distribution at steady-state, rather than Vd) could account for the observed discrepancies. It can be concluded that the latter were probably related to the characteristics of the populations investigated: it is unclear, for example, whether the elderly patients included in the earlier study were ambulant or bedridden and whether they were receiving associated drug therapy (although it was stated that none was taking drugs 'likely to interact' with VPA).…”
Section: Resultsmentioning
confidence: 99%
“…Differences between the control groups (e.g. in alcohol intake) should be considered, especially in view of the fact that the young volunteers included in the Bryson et al (1983) study showed unusually short VPA halflives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Valproate does not induce hepatic enzymes but it is associated with reduction in bone mineral density through reduction in osteoblastic function. 35,36,43 Its other important side effects in the elderly include dosedependent tremor and reversible parkinsonism.…”
Section: Valproic Acidmentioning
confidence: 99%
“…With increased age, the elimination half-life of VAL can be prolonged [42], and the free fraction of plasma concentrations increases [43]. Aspirin can increase the VAL free fraction [44].…”
Section: Anticonvulsantsmentioning
confidence: 99%